Neuroprotective effects of açaí (Euterpe oleracea Mart.) against diabetic retinopathy - de Oliveira, Edwiges de Fátima; Brasil, Alódia; Herculano, Anderson Manoel; Rosa, Matheus A.; Gomes, Bruno Duarte; Rocha, Fernando Allan de Farias (Frontiers in Pharmacology, 2023)
Diabetes describes a metabolic disorder of multiple etiologies, characterized by chronic hyperglycemia, which induces a series of molecular events capable of leading to microvascular damage, affecting the blood vessels of the retina, causing diabetic retinopathy. Studies indicate that oxidative stress plays a central role in complications involving diabetes. Açaí (Euterpe oleracea) has attracted much attention given its antioxidant capacity and potential associated health benefits in preventing oxidative stress, one of the causes of diabetic retinopathy. The objective of this work was to evaluate the possible protective effect of açaí on the retinal function of mice with induced diabetes, based on full field electroretinogram (ffERG). We opted for mouse models with induced diabetes by administration of a 2% alloxan aqueous solution and treatment with feed enriched with açaí pulp. The animals were divided into 4 groups: CTR (received commercial ration), DM (received commercial ration), DM + açaí (açaí-enriched ration) and CTR + açaí (açaí-enriched ration). The ffERG was recorded three times, 30, 45 and 60 days after diabetes induction, under scotopic and photopic conditions to access rod, mixed and cone responses, in addition to monitoring the weight and blood glucose of the animals during the study period. Statistical analysis was performed using the two-way ANOVA test with Tukey's post-test. Our work obtained satisfactory results with the ffERG responses in diabetic animals treated with açaí, where it was observed that there was no significant decrease in the b wave ffERG amplitude of this group over time when compared to the results of the Diabetic group not treated with açaí, which showed a significant reduction of this ffERG component. The results of the present study show, for the first time, that treatment with an açaí-enriched diet is effective against the decrease in the amplitude of visual electrophysiological responses in animals with induced diabetes, which opens a new horizon for the prevention of retinal damage in diabetic individuals from treatment with açaí base. However, it is worth mentioning that our findings consist of a preliminary study and further researches and clinical trials are needed to examine açaí potential as alternative therapy for diabetic retinopathy.